A Survey of Research on Montagnais and Naskapi (Innu-aimun) in Labrador - MacKenzie, Marguerite (Atlantic Provinces Linguistic Association, 1991)
The last two decades have seen increased interest in the study of the language o f the Innu of Labrador. Researchers from Memorial University of Newfoundland have been prominent in producing descriptions of grammar, lexicon and linguistic variation in the community of Sheshatshit. Anthropologists have been active in the collection of texts and toponyms. This article gives an overview of work to date in these areas.